2021
DOI: 10.1186/s12879-021-06697-1
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in intravenous drug abusers: clinical challenges emerging from a single-centre experience

Abstract: Background Intravenous drug abuse (IDA) is a known risk factor for infective endocarditis (IE) and is associated with frequent relapses, but its prognostic impact is still debated. The potential futility of surgery in this population is a further issue under discussion. We aimed to describe the clinical characteristics, the therapeutic strategy, and the prognosis associated with IDA in IE. Methods We retrospectively analysed 440 patients admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…IVDU is a widely recognized predisposing factor of IE, with an annual incidence of 1-5% in this population (4). It has been suggested that endothelial injury from injected particulate matter, direct injection of contaminated material, and drugassociated vasospasm leading to intimal damage and thrombus formation can lead to endocarditis with IVDU (5). Acquired aortic root to right ventricular communications are rare but can occur as stulisation from IE, as in our case.…”
Section: Discussionmentioning
confidence: 64%
“…IVDU is a widely recognized predisposing factor of IE, with an annual incidence of 1-5% in this population (4). It has been suggested that endothelial injury from injected particulate matter, direct injection of contaminated material, and drugassociated vasospasm leading to intimal damage and thrombus formation can lead to endocarditis with IVDU (5). Acquired aortic root to right ventricular communications are rare but can occur as stulisation from IE, as in our case.…”
Section: Discussionmentioning
confidence: 64%
“…Compared to left-sided IE, right-sided IE is more commonly linked to intravenous drug use (IVDU), central venous catheters, and intracardiac devices, which have become more prevalent in recent years [ 6 ]. Right-sided IE accounts for 5-10% of all cases of IE, and IVDU is considered a strong risk factor for such an infection [ 6 - 7 ]. It is commonly observed that the tricuspid valve is most often affected in cases of endocarditis in IVDU, followed by the mitral and aortic valves [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Mathew et al has shown that among injection drug users, the pulmonary valve is involved in only a small number of cases [ 8 ]. IVDU increases the likelihood of introducing bacteria and other foreign organisms into the bloodstream, which can then infect the heart valves [ 7 ]. In addition, individuals who use IVDU may also have weakened immune systems, making them more susceptible to bacterial and fungal infections [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation